The Influence of Gross Regional Domestic Product Per Capita and Foreign Direct Investment on Income Inequality: An Empirical Study of 34 Provinces in Indonesia - Maichal, Maichal; Hartono, Powell Gian; Firman, Afrizal; Yudha, I Made Endra Kartika (Universitas Muhammadiyah Yogyakarta, 2024)
The study investigates the correlation between Gross Regional Domestic Product (GRDP) per capita, Foreign Direct Investment (FDI), and the Gini coefficient using panel data from 34 provinces in Indonesia from 2015 to 2023. A panel data regression analysis method was employed for data processing to optimize estimation results. The results obtained from the analysis using the Fixed Effects Model (FEM) consistently show strong positive outcomes. The findings imply a direct connection between higher GRDP per capita, increased FDI, and a higher Gini coefficient, suggesting that more significant foreign investment and higher per capita GDP contribute to increased income inequality across the Indonesian provinces. The study emphasizes the critical role of regional governments in addressing these disparities. It suggests strategies such as implementing regional policies to boost investment, enhancing infrastructure, creating more business opportunities, and promoting tourism. The proposal to establish the National Capital City (IKN) in East Kalimantan is presented as a long-term solution to reduce income inequality among the provinces.